PENERAPAN KONSEP COMFORT OF HUMAN CIRCULATION DAN ARSITEKTUR NEO VERNAKULAR PADA REDESAIN PASAR TRADISIONAL DESA SAYAN - I Wayan Wirya Sastrawan; I Gede Surya Darmawan; I Gusti Agung Gede Wisnu Kusuma Dwipayana (Jurnal Anala, 2024)
Traditional markets are places where buying and selling transactions take place between traders and buyers by implementing a bargaining system that is characteristic of traditional markets. Many people depend on the existence of traditional markets. Especially for lower middle class people. Sayan Village Traditional Market, Ubud District, Gianyar Regency is a location for trading daily necessities such as fruit, vegetables, meat, prayer tools, and others. The problems faced by this market are unhygienic market conditions and the appearance of slums, buildings and spatial layout. Sayan Market experiences an inadequate and disorganized condition, with a number of areas not being utilized optimally, such as chaotic parking and kiosk facilities and main market stalls that are neglected and not well maintained. This can cause people to feel uncomfortable, and people prefer modern markets that prioritize cleanliness. The research method used by the author to prepare this research is a qualitative method in the form of literature study, observation, documentation and interviews. Based on the existing problems, it is necessary to redesign the Traditional Market in Sayan Village, Ubud District, Gianyar Regency so that it can accommodate functions well packaged in a new, clean, comfortable market appearance and pay attention to more optimal circulation